Intersectional Positionality and Lived Experiences of Asian International Teacher Educators in U.S. Academia - Kheirkhah, Haniyeh (Journal of Ethnic and Cultural Studies, 2026)
This study, part of a larger research project, examines the intersectional identities of Asian international teacher educators (AITEs) in U.S. higher education. Grounded in Crenshaw’s (2013) framework of intersectionality, the study explores how AITEs experience systemic marginalization, racialization, and linguistic prejudice in academic spaces, and how these experiences inform their equity-oriented pedagogical approaches. Drawing on semi-structured interviews with six AITEs, the study investigates how intersecting identities shape their professional roles and pedagogical practices. Using an intersectional qualitative methodology that integrates narrative inquiry, document analysis, and thematic analysis, the findings reveal how AITEs negotiate invisibility, institutional constraints, and discrimination. Despite racial, linguistic, and gendered challenges that undermine professional credibility, participants resist marginalization by drawing on non-Western epistemologies, fostering inclusive dialogue, and contesting Eurocentric frameworks. By recognizing their positionality as AITEs and cultivating critical consciousness, participants engage in transformative acts of resistance and liberation. Their identities remain fluid across transnational contexts, positioning them as cultural and epistemological bridges (Coll et al., 2012). This study contributes to scholarship on AITEs’ intersectional experiences and advances critical multicultural education and institutional reform in higher education.